PENGARUH MOTIVASI KERJA, KERJA SAMA TIM, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI NON PNS RSUD dr. ABDOER RAHEM SITUBONDO DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Ralda Cigra Novantri; Randika Fandiyanto; Triska Dewi Pramitasari (Fakultas Ekonomi dan Bisnis, 2025)
Dr. Abdoer Rahem Situbondo Regional General Hospital (RSUD) as one of the government-owned health facilities has a strategic role in providing health services to the community. The purpose of this study is to analyze and test the effect of Work Motivation, Teamwork, and Work Environment on the Performance of Non-PNS Employees of Dr. Abdoer Rahem Situbondo Regional General Hospital with Job Satisfaction as an Intervening Variable. The population in this study were NON-PNS employees of Dr. Abdoer Rahem Situbondo. The sampling technique used simple random sampling technique. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the hypothesis test using the Smart PLS 3.0 application show that work motivation has a significant positive effect on job satisfaction, teamwork has a positive but not significant effect on job satisfaction, work environment has a significant positive effect on job satisfaction, work motivation has a significant positive effect on performance, teamwork has a significant positive effect on performance, work environment has a significant negative effect on performance, job satisfaction has a significant positive effect on performance, work motivation has a significant positive effect on performance through job satisfaction, teamwork has a positive but not significant effect on performance through job satisfaction, work environment has a significant positive effect on performance through job satisfaction.